Statistical mechanics - McQuarrie, Donald A (New Delhi : Viva Books., 2003)
It is ideal for a senior or first-year graduate level courses. Statistical Mechanics is the extended version of McQuarrie"s 1984 text -- Statistical Thermodynamics -- now out of print. Although our printing of this book carries a 2000 copyright date, this is not a new edition. It is the original first edition, without any changes to the text (except preface). Despite its age, it is still a renowned and accessible introduction to the subject, containing a large number of chapter-ending problems for students.
Appendix A-K 593-630p.; Index 631-641p.; Reprint 2015.
Keywords: Chemical equilibrium; Continuum mechanics; Chemistry